Ventilation History of the Nordic Seas Deduced From Pelagic‐Benthic Radiocarbon Age Offsets. (13th April 2021) - Telesiński, Maciej M.; Ezat, Mohamed M.; Muschitiello, Francesco; Bauch, Henning A.; Spielhagen, Robert F.
Abstract: Changes in ocean circulation are considered a major driver of centennial‐to‐millennial scale climate variability during the last deglaciation. Using four sediment records from the Nordic Seas, we studied radiocarbon ventilation ages in subsurface and bottom waters to reconstruct past variations in watermass overturning. Planktic foraminiferal ages show significant spatial variability over most of the studied period. These differences suggest that the ventilation of the shallower subsurface waters is strongly influenced by local conditions such as sea‐ice and meltwater input, changes in mixed‐layer depth, and/or variable contributions of water masses with different 14 C signatures. Despite covering a significant water depth range, the benthic foraminiferal records show common long‐term patterns, with generally weaker ventilation during stadials and stronger during interstadials. The Greenland Sea record differs the most from the other records, which can be explained by the greater depth and the geographical distance of this site. The benthic records reflect regional shifts in deep convection and suggest that the deep Nordic Seas have been generally bathed by a single, though changing, deep‐water mass analogous to the present‐day Greenland Sea Deep Water. Since significant offsets in ventilation ages are yielded by different taxonomic or ecological groups of benthic foraminifera, the use of uniform material seems a prerequisite to reconstruct bottom water ventilation histories. Plain Language Summary: Earth's climate is tightly coupled with the global ocean conveyor belt. To understand climate changes, we need to reconstruct past ocean circulation. A suitable place to perform such studies is the Nordic Seas. We analyze four sediment records of the last deglaciation (∼20–10 thousand years ago) during which the Earth's climate experienced a transition from an ice age to a warm period, with several plot twists in between. We compare radiocarbon ages of shells of organisms that have lived on the bottom of the sea and close to its surface. As these fossils are found in the same sediment layers, they lived at the same time in the geological past. However, their radiocarbon ages differ. The amount of this difference depends on the intensity of water exchange between the surface and the bottom of the ocean. From the difference we infer the pace of deep‐water formation. Our results show intensive ocean circulation during the relatively warm periods and a weaker exchange of water masses during relatively cold periods. The outcomes of our study might help to improve computer models of the ocean‐climate system and allow us to predict with greater confidence its changes in the future. Key Points: We present four radiocarbon ventilation age records of subsurface and bottom waters from the Nordic Seas since the Last Glacial Maximum Planktic records are generally older than modern but show significant spatial variability, indicating the influence of local conditions in some intervals Benthic records show weaker ventilation during stadials and stronger during interstadials, reflecting shifts in overturning circulation